Gerald Nelson discusses article "Do roads cause deforestation?" - Nelson, Gerald C. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2011)
IFPRI Senior Researcher, Gerald Nelson, discusses the article, "Do roads cause deforestation." On July 25, 2011, Nelson and co-author, Daniel Hellerstein, were honored by the AAEA with the Publication of Enduring Quality Award for this innovative 1997 publication on techniques for turning satellite imagery into economic data.